GENRES OF ASANTE ORAL LITERATURE: PRESERVING THE CULTURAL HERITAGE OF THE ASANTES OF GHANA - Asantewaa Abena Sampene, Akua; Adom, Dickson; Kquofi, Steve; Baah Owusu Panin, Kwame (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The Asante society depended on oral traditions to go through their activities until formal education was introduced. Asante oral literature had almost completely been overlooked and almost forgotten with the influence of globalization and western culture where people would be aliens in their own motherlands. Therefore, the purpose of the research is to fill the academic vacuum through this study for oral literature to serve its purpose fully in the Asante culture by giving attention it requires as a discipline of humanities. The study focused on qualitative case study and phenomenological study exploring the genres of Asante oral literature and provided viable and appealing ways for preserving and transmitting them to the modern generations to come. Snowballing under purposive sampling was employed with data collection instruments of questionnaires, interviews, focus groups and observation generated from 18 conveniently sampled respondents. The outcome of the study showed that oral tradition could be a hybrid of traditional writing, visual and audio methods on CDs and DVDs to enhance the preservation and also be shared on almost all social media platforms to inform people about the traditions and customs of the Asante land. The study recommends researchers consider new trends of packaging oral literature to suit users.